2020
DOI: 10.1088/2053-1591/ab6a53
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into corrosion and wear behaviors of laser-clad coatings on Ti6Al4V

Abstract: TiAlCoCr x FeNihigh-entropy alloys (HEAs) coatings were fabricated on the surface of Ti6Al4V by laser cladding. Their microstructural evolution with the increase in x value (x=0, x=1.0, x=2.0) was investigated in detail. Besides that, the investigation into the effects of the Cr content on their corrosion behaviors and mechanical properties (in terms of hardness and wear resistance) was also carried out comprehensively. The results indicated that two kinds of phases (a solid solution with thehexagonal cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The Ti elements were prone to generate the more common Ti-containing ceramic phases. [55,56] For example, Liu et al [56] prepared CoCrFeMnNiTi x (x = 0, 0.25, 0.5, 0.75, or 1) HEA-LC coatings on a 40Cr substrate. When considering the effect of the dilution ratio, the proportion of iron atoms in the raw material was appropriately reduced.…”
Section: Dual-phase and Multiphase High-entropy Alloy Coatingsmentioning
confidence: 99%
“…The Ti elements were prone to generate the more common Ti-containing ceramic phases. [55,56] For example, Liu et al [56] prepared CoCrFeMnNiTi x (x = 0, 0.25, 0.5, 0.75, or 1) HEA-LC coatings on a 40Cr substrate. When considering the effect of the dilution ratio, the proportion of iron atoms in the raw material was appropriately reduced.…”
Section: Dual-phase and Multiphase High-entropy Alloy Coatingsmentioning
confidence: 99%
“…When subjected to wear tests for 180 min in air, the friction coefficient of the coating (0.61) was significantly lower than that of the substrate (1.04), and its wear volume (0.823 ± 0.012 mm 3 ) was reduced by 48% relative to that of the substrate (2.329 ± 0.025 mm 3 ). Zhang et al [41] prepared TiAlCoCr 2 FeNi HEA coating that contained an HCP solid solution by laser cladding on Ti6Al4V. Dry-sliding wear tests performed for 2 h demonstrated that the wear resistance of Ti6Al4V was considerably improved by laser cladding the HEA coating because the wear volume of the coating was approximately 40% that of Ti6Al4V.…”
Section: Introductionmentioning
confidence: 99%
“…therefore, a suitable surface modification needs to be implemented to protect from undesired material loss. in recent years, many surface modification techniques were attempted to improve the surface properties of titanium alloys such as chemical vapour deposition, physical vapour deposition, micro-arc oxidation, electroplating, laser modification and plasma transferred arc (Pta) process [3][4][5][6][7][8][9]. among these techniques, Pta based surface modification was attracted much attention due to high efficiency, good metallurgical bond, low cost and easy operation.…”
Section: Introductionmentioning
confidence: 99%